Control of regulated and unregulated emissions of an automotive spark ignition engine with alternative fuels (methanol, ethanol and hydrogen) - Akshey Marwaha; K.A. Subramanian (Measurement: Energy)
The present research study investigates the effect of alternative fuels (Methanol, Ethanol, Hydrogen) on the performance, combustion, and emission (regulated and unregulated) characteristics of an automotive spark ignition engine. The FTIR (Fourier Transform Infrared) spectrometer was used to measure instantaneous emissions with a frequency of 5. The regulated (carbon monoxide, acetylene, ethene, propene, nitric oxide, nitrogen dioxide) and the unregulated (methane, hydrogen cyanide, nitrous oxide) emissions with ethanol, methanol, and hydrogen are compared with base gasoline. The engine was run at a constant speed of 3500 rpm. The brake thermal efficiency (BTE) was enhanced by 1.2 %, 2.9 %, and 25.9 % with ethanol, methanol, and hydrogen compared to gasoline. The experimental results indicate that the acetylene, propene, methane, and hydrogen cyanide emissions were reduced to zero levels with methanol. Acetylene emissions decreased by 25.3 % and 61.6 % with ethanol and hydrogen compared to base gasoline. The propene emissions were zero with ethanol and methanol. Nitric oxide emissions decreased by 62.4 % and 98.9 % with ethanol and methanol. Hydrogen cyanide emissions decreased by 20 % with hydrogen and to zero with methanol. Nitrogen dioxide emissions decreased by 65.6 % with ethanol. Nitrous oxide emissions decreased by 38.8 %, 75.4 %, and 32.1 % with ethanol, methanol, and hydrogen. Hence, the regulated and unregulated emissions from combustion engines could be controlled and reduced to a minimal level along with enhanced thermal efficiency using alternative fuels such as methanol, ethanol, and hydrogen.